2020
DOI: 10.1016/j.yjmcc.2019.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of human cardiac progenitor cells into cardiac pacemaker-like cells

Abstract: We used a screening strategy to test for reprogramming factors for the conversion of human cardiac progenitor cells (CPCs) into Pacemaker-like cells. Human transcription factors SHOX2, TBX3, TBX5, TBX18, and the channel protein HCN2, were transiently induced as single factors and in trio combinations into CPCs, first transduced with the connexin 30.2 (CX30.2) mCherry reporter. Following screens for reporter CX30.2 mCherry gene activation and FACS enrichment, we observed the definitive expression of many pacema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…In addition, some other types of stem cells were used to convert mature myocytes into SAN-like cells. The integration of TBX5 (SHT5), HCN2, and SHOX2 transcription factors and channel proteins has been suggested as a promising stem cell therapy for SSS and CPCs can be reprogrammed to serve as pacemaker-like cells using this approach [ 32 ]. Several research reports have demonstrated the forward programming of pluripotent stem cells (PSCs) with Tbx3 [ 33 ] or SHOX2 [ 34 ] and in vivo transformation of commonly existing contractible cardiomyocytes to pacemaker-like cells via the elevated Tbx18 expression, the main transcriptional factor involved in the progression of SAN [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some other types of stem cells were used to convert mature myocytes into SAN-like cells. The integration of TBX5 (SHT5), HCN2, and SHOX2 transcription factors and channel proteins has been suggested as a promising stem cell therapy for SSS and CPCs can be reprogrammed to serve as pacemaker-like cells using this approach [ 32 ]. Several research reports have demonstrated the forward programming of pluripotent stem cells (PSCs) with Tbx3 [ 33 ] or SHOX2 [ 34 ] and in vivo transformation of commonly existing contractible cardiomyocytes to pacemaker-like cells via the elevated Tbx18 expression, the main transcriptional factor involved in the progression of SAN [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though directed cardiomyogenesis from fibroblasts was significantly enhanced in the last few years by reprogramming with several cardiopoietic transcription factor combinations (Ieda et al, 2010;Inagawa et al, 2012;Protze et al, 2012;Qian et al, 2012;Christoforou et al, 2013), targeted differentiation of fibroblasts or working cardiomyocytes into PCs, particularly SAN and AVN cells, remains to be poorly studied. It is known that PC development and differentiation are significantly modulated by specific transcriptional regulators, among them SHOX2, TBX3, TBX5, and TBX18 (Blaschke et al, 2007;Christoffels et al, 2010;Munshi, 2012;Cho, 2015;Gorabi et al, 2019a,b;Raghunathan et al, 2020;van Eif et al, 2020). Hoogaars et al (2007) performed a fundamental study on the role of the transcriptional repressor TBX3 in the development of the cardiac conduction system.…”
Section: Transcription Factor-based Reprogramming Approachesmentioning
confidence: 99%
“…Integrating previously generated scRNAseq on LV cells at p1, p4, p7, and p14 with new data at p56, they identified fibroblasts as a crucial cell type promoting CM differentiation, which they confirmed in vitro with the co-culture of immature CM, isolated from p1 pups, with neonatal or adult fibroblasts. Single-cell analysis has been also used to analyze the reverse process of adult CM reprogramming to mCPs [ 77 ] as well as assess the negative effects of nicotine on hESC differentiating into CMs [ 78 ], proving to be a valid platform to determine embryonic toxicity; and to establish the best combination of transcription factors to obtain pacemaker-like cells from Nkx2-5 + CPs, which are derived from the transdifferentiation of adult human adipogenic MSCs (hASMSCs) [ 79 ].…”
Section: Cardiac Scrnaseq To Elucidate In Vitro Differentiation Anmentioning
confidence: 99%